Screening Mild and Major Neurocognitive Disorders in Parkinson’s Disease - Tivadar Lucza; Kázmér Karádi; János Kállai; Rita Weintraut; József Janszky; Attila Makkos; Sámuel Komoly; Norbert Kovács (Behavioural Neurology)
Introduction. Among the nonmotor features of Parkinson’s disease (PD), cognitive impairment is one of the most troublesome problems. New diagnostic criteria for mild and major neurocognitive disorder (NCD) in PD were established by Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM-5). The aim of our study was to establish the diagnostic accuracy of widely used screening tests for NCD in PD. Methods. Within the scope of our study we evaluated the sensitivity and specificity of different neuropsychological tests (Addenbrooke’s Cognitive Examination (ACE), Mattis Dementia Rating Scale (MDRS), Mini Mental State Examination (MMSE), and Montreal Cognitive Assessment (MoCA)) in 370 PD patients without depression. Results. MoCA and ACE feature the finest diagnostic accuracy for detecting mild cognitive disorder in PD (DSM-5) at the cut-off scores of 23.5 and 83.5 points, respectively. The diagnostic accuracy of these tests was 0.859 (95% CI: 0.818–0.894, MoCA) and 0.820 (95% CI: 0.774–0.859, ACE). In the detection of major NCD (DSM-5), MoCA and MDRS tests exhibited the best diagnostic accuracy at the cut-off scores of 20.5 and 132.5 points, respectively. The diagnostic accuracy of these tests was 0.863 (95% CI: 0.823–0.897, MoCA) and 0.830 (95% CI: 0.785–0.869, MDRS). Conclusion. Our study demonstrated that the MoCA may be the most suitable test for detecting mild and major NCD in PD.